How the secrets of the Black Death give us sustainable meat. (10th March 2023) - Peters, Daniel; Lakey, Jeremy
Abstract : Pathogenic bacteria such as Yersinia pestis, causative agent of the plague, have a genetic armoury of proteins they use to defend themselves against the immune system when invading a host. Upon invasion, Y. pestis bacteria deploy a molecular cloaking device, made of a protein called Caf1, which allows them to avoid being eaten by a host's macrophage cells. Caf1 has several interesting structural properties that allow it to carry out this role, such as its 'non-stick', bioinert nature. This provides us with a blank canvas for protein engineering, where we can insert different bioactive signals into the protein structure, allowing us to instruct cells in a defined way, e.g., providing them with attachment sites or behavioural cues. We can also exploit Caf1's unusual properties to use it as a molecular Lego kit, mixing and matching different bioactive Caf1 modules to make multifunctional biomaterials. We aim to use engineered Caf1 proteins to solve problems in the industrial scale production of cells for technologies such as cell therapy and cultivated meat. For example, by mixing adhesive and growth factor signals in a single material, and displaying multiple copies of each signal at once, we can reduce the number of expensive reagents needed. More generally, Caf1 is an excellent example of how bacterial armaments and defences can be re-engineered and adapted to benefit society, rather than cause disease.